Down-regulation of hepatitis delta virus super-infection in the woodchuck model. - Lukash, Tetyana (Virology, 2019)
Mechanisms mediating clearance of hepatitis delta virus (HDV) are poorly understood. This study analyzed in detail profound down-regulation of HDV infection in the woodchuck model. Super-infection with HDV of woodchucks chronically infected with HBV-related woodchuck hepatitis virus produced two patterns. In the first, HDV viremia had a sharp peak followed by a considerable decline, and initial rise of HDV virions’ infectivity followed by abrupt infectivity loss. In the second, HDV titer rose and later displayed plateau-like profile with high HDV levels; and HDV infectivity became persistently high when HDV titer reached the plateau. The infectivity loss was not due to defects in the virions’ envelope, binding to anti-envelope antibodies, or mutations in HDV genome, but it correlated with profound reduction of the replication capacity of virion-associated HDV genomes. Subsequent finding that in virions with reduced infectivity most HDV RNAs were not full-length genomes suggests possible HDV clearance via RNA fragmentation.